Correction to McKelvey and Page, "Public and Private Information: An Experimental Study of Information Pooling" - Hanson, Robin (Econometrica, 1996)
The above mentioned article, McKelvey and Page (1990), errs in calculating the consequences of myopicrational responses to the payoffs used in the experiments it describes. This invalidates the article’s proof that myopic responses are a non-myopic Bayes-Nash equilibrium. Thus we lack game-theoretical predictions to compare with their experimental results. In their article, McKelvey and Page note that